A performance-based subsidy allocation of ferry transportation: A data envelopment approach. (30th September 2018) - Yu, Ming-Miin; Chen, Li-Hsueh; Hsiao, Bo
Abstract: Ferry transportation plays an essential role in transportation services between a mainland and its offshore islands, as well as among those islands. However, low volume routes frequently operate at a loss because they are socially necessary but not profitable. Thus, a government may provide financial support to such ferry routes. Since budgetary resources for offshore ferry routes are limited, this paper offers a performance-based method constructed through data envelopment analysis to help governments allocate subsidies to individual offshore ferry routes. The proposed method considers the concepts of cross-efficiency and structural efficiency, simultaneously. The allocation results for a current ferry subsidy allocation policy and the proposed method are compared. The results may provide valuable suggestions for allocation policies for subsidies to ferry firm. Highlights: A new performance-based subsidy allocation method is proposed. The proposed method is based on the data envelopment analysis model. The concepts of cross-efficiency and structural efficiency are considered. A case study of offshore ferry routes in Taiwan is applied for subsidy allocation. The proposed method is more easily implemented than the current policy.